A survey of antibiotics prescribing practices of dentists in Kerala state - Faizal C Peedikayil; Arun Narayan (Wolters Kluwer Medknow Publications, 2012)
Background: The discovery of antibiotics marked a watershed in the treatment of infections. But the inappropriate use of antibiotics has contributed to the worldwide problem of antimicrobial resistance. Information on the knowledge, understanding and use of antibiotics by dental practitioners is scarce. This study assessed the antibiotic prescription patterns of dental practitioners in Kerala state , India . Information was collected via a questionnaire distributed to the participants of 43rd Kerala State Dental Conference at Manjeri, Kerala, India. The geographical distribution of the dentists who participated in this questionnaire are dental surgeons from Kerala state in India who are the members of Indian dental association. Method: The questionnaire was designed to investigate general dental practitioners' knowledge of antibiotics prescription for a number of clinical signs that may be associated with a dental infection. Dental surgeons were also asked whether some clinical conditions required antibiotics and their choice of treatment if any. questionnaires were analyzed and the responses to each question expressed as absolute frequencies in SPSS database. The cases and the antibiotics prescribed by dentists for each case were determined by the descriptive statistics method ie frequency. Results: Of the 300 questionnaires delivered 248 (82%) respondents returned fully completed forms. Antibiotic use varied for different clinical sitautions. Amoxycillin is the most widely used antibiotic for dental infections. Conclusion: This study shows that the antibiotics are used in many conditions which are not indicated in normal situations. There has been an overuse of antibiotics